Perilaku Komunikasi Siswa SMA-MA Di Daerah Aliran Sungai (Das) Dalam Bermain Esports (Studi Etika Sosial Siswa di Palangka Raya) - Mikdar, U.Z.; Wisman, Yossita; Dony, Garry William; Bernisa, Bernisa (Jurnal Ilmiah Kanderang Tingang, 2025)
The problem of this research is related to students' communication behavior in playing ESPORTS and its impact on students' daily lives, while the aim is to describe the picture of students' communication behavior in playing ESPORTS and its impact on communication behavior in everyday life. This research includes qualitative descriptive research using Miles and Huberman's interactive data analysis techniques. The subjects and informants were students from State High School 10 (SMAN 10), Madrasah Aliyah (MA) Miftahul Jannah, and Al-Ishlah Vocational High School (SMK) located in the Palangka Raya Watershed (DAS), totaling 30 people. which consists of SMAN 10 containing 10 people, MA 10 people, and SMK 10 people. With several types of games chosen by students such as Mobile Legends, Free Fire, Genshin Impact, HOK, Roblox, FC Mobile, The Spike, Clash of Clans, CODM, Terraria. The results of his research show that the communication behavior of high school, MA and vocational school students in the Palangka Raya River Basin (DAS) who play ESPORTS is as follows; (1) Sometimes when playing or leaving a game, speak harshly, shout, hit the table or wall. Even these harsh words sometimes carry over into everyday life even if they are only limited to close friends; and (2) the positive impact is that playing ESPORTS can relieve stress, eliminate feelings of loneliness and be entertained, while the negative impact is that it sometimes causes lack of sleep, emotions, and also disrupts prayer times.